Tindak tutur Ilokusi dalam cerpen القط والكلب perspektif teori John Searle - Kamal, Muhammad Zulfa (Maliki Interdisciplinary Journal, 2026)
This study aims to reveal the forms of illocutionary acts and their types in the short story القط والكلب. The theory used in this study is the theory of illocutionary speech acts proposed by John Searle. This study uses a qualitative descriptive method. The research method used is a qualitative descriptive method by implementing a literature review. Data collection in this study uses reading and note-taking techniques, then analyzed with the stages of data identification, data presentation, and conclusion drawing. The results of the study are in the form of four utterances spoken by characters in the short story. The four utterances are then classified into Searle’s illocutionary theory. Two utterances are classified into assertives, one utterance is classified into commissives and one utterance is included in the directive type. The data analysis technique includes three stages: transcription of the short story text, classification and tabulation of data and analysis of illocutionary acts in the short story القط والكلب. The research results show that the short story contains three of the five types of illocutionary acts proposed by John Searle in his theory. Each type of illocutionary act in the speech can be categorized based on the type of speech.